SOCIO-PHILOSOPHICAL PROBLEMS OF THE HIGHER VOCATIONAL EDUCATION IN THE CONTEXT OF CULTURE CRISIS - V. L. Benin; O. V. Frolov (Russian State Vocational Pedagogical University, 2015)
The paper looks at the urgent problems of the Russian higher vocational school from a philosophical and social viewpoint, and maintains that its current situation and prospects should be analyzed in the context of complicated social processes and socio-economic reorganizations undertaken at the turn of the 20th - 21st centuries. Facing a cultural crisis, the Russian society requires new cultural, political, economic and social ways out. The research shows that a considerable decline in the specialists' competence level results from the low education quality requirements and decreasing social status of vocational education. The authors emphasize the culture study aspects of professional activity and regard them as the basis for vocational training quality assurance aimed at raising the professional competence. In authors' opinion, the aspect of culture studies remains the most important in the process of liberalization and humanization of vocational education, since the modern culture is an effective instrument of world perfection as well as students' self-development and self-understanding.